(untitled) (African Disability Rights Yearbook, 2021)
A major social challenge to the implementation of the Convention on the Rights of Persons with Disabilities (CRPD) in Africa relates to the widespread stigma attached to the characteristics of disability and those who embody them. The article (a) discusses the phenomenon of social stigma as an underlying contextual lens around Africans with disabilities; (b) examines how stigma generally impacts the lives of Africans with disabilities; (c) applies (a) and (b) to the illustrative examples of stigma related to the treatment of people with albinism in Tanzania, persons with leprosy in Nigeria, and general perceptions of disability in Kenya; and (d) suggests several ways forward to diminish and eventually eradicate the significant damaging effects of stigma attached to disability characteristics and the Africans who live with disabilities, thereby paving the way for increased and more effective implementation of the CRPD in Africa.